PTU-079 Over-age self referrals in the english bowel cancer screening programme – are they the worried well or the symptomatic needing something more?. (17th June 2017) - Chapman, CJ; Field, A; Logan, RF
Abstract : Introduction: The English Bowel Cancer screening programme has been in operation in England since 2006. Subjects aged 60–74 and who are registered with an NHS general practice are invited to complete a guaiac faecal occult blood test (FOBt) every two years until they reach 75. People found to have abnormal tests are then referred to for further assessment, with most going on to have a colonoscopy. Over the age of 75, individuals can 'self-refer' into the programme. The size of the population >75 is increasing, and is more health conscious. We were therefore interested in understanding the demographics of this group of individuals. Method: The number of people aged 75 and over, who requested kits within the Eastern hub area of the BCSP, was interrogated. Data was analysed according to age, gender, positivity of the test, fitness for colonoscopy and cancers and adenomas detected. Results: Between 2010 and 2015 over 30 000 tests were completed by subjects with ages ranging from 75% to 98. 54% of individuals were male compared to 49% in 60–74 age group. Numbers of people who self-refer are increasing annually but still represent less than 2% of all tests performed. Positivity in the over 75's was 3.3% compared to 2% in the 60–74 age range. Cancer detection rates were higher in these individuals than in the younger age groups (cancer: 16% vs 8.5%). Conclusion: Whilst numbers of over age referrals are on the increase they remain a small proportion of the subject screened by the BCSP. As might be expected from an older population a higher cancer and adenoma detection rate was observed. If uptake continues to increase, it is likely to impact on the colonoscopy services in England. Disclosure of Interest: None Declared